Safety of Lactobacillus plantarum ST8Sh and Its Bacteriocin - Todorov, Svetoslav Dimitrov; Perin, Luana M.; Carneiro, Bruno M. [UNESP]; Rahal, Paula [UNESP]; Holzapfel, Wilhelm; Nero, Luís Augusto (Springer Nature, 2017)
Total DNA extracted from Lb. plantarum ST8Sh was screened for the presence of more than 50 genes related to production of biogenic amines (histidine decarboxylase, tyrosine decarboxylase, and ornithine decarboxylase), virulence factors (sex pheromones, gelatinase, cytolysin, hyaluronidase, aggregation substance, enterococcal surface protein, endocarditis antigen, adhesion of collagen, integration factors), and antibiotic resistance (vancomycin, tetracycline, erythromycin, gentamicin, chloramphenicol, bacitracin). Lb. plantarum ST8Sh showed a low presence of virulence genes. Only 13 genes were detected (related to sex pheromones, aggregation substance, adhesion of collagen, tetracycline, gentamicin, chloramphenicol, erythromycin, but not to vancomycin, and bacitracin) and may be considered as indication of safety for application in fermented food products. In addition, interaction between Lb. plantarum ST8Sh and drugs from different groups were determined in order to establish possible application of the strain in combination with commercial drugs. Cytotoxicity of the semi-purified bacteriocins produced by Lb. plantarum ST8Sh was depended on applied concentration—highly cytotoxic when applied at 25 μg/mL and no cytotoxicity at 5 μg/mL.
Keywords: Bacteriocins; Cytotoxicity; Lactobacillus plantarum; Probiotics; Safety; Virulence